Deteksi Kandungan Daging Babi pada Bakso yang Dijajakan di Pusat Kota Salatiga Menggunakan Teknik Polymerase Chain Reaction - Fidia Fibriana; Tuti Widianti; Amin Retnoningsih (Biosaintifika: Journal of Biology & Biology Education)
The purpose of this research is to determine whether the meatball products that sold atSalatiga are contain pork. Stratifi ed random sampling technique used to take samplesof meatballs which sold by 13 meatball stalls from 25 meatball stalls scattered in thecentral city of Salatiga. Isolation and purifi cation of DNA from meatballs, beef, andpork samples use Sambrook et al. modifi ed by Sulandari and Zein method. The yield ofDNA followed by PCR process using P14 primers that representing the PRE-1 loci in thepig genome. DNA amplifi cation used protocol initial denaturation at temperature of 93°C for 2 minutes, followed by 45 cycles of denaturation 93 °C for 1 minute, annealing62 °C for 30 seconds, extension 72 °C for 1 minute, and ending extension 72 °C for 2minutes. Appearance of 481 base-pair PCR product was expected. Result from 1,2%agarose gel electrophoresis of PCR products showed 481 base-pair, a specifi c DNAband size in pork meat and meatball samples number thirteen. It can be concluded thatmeatball product from meatball stall number thirteen was contain pork. Keywords: detection of pork, meatball products, PCR technique